169k views
4 votes
Can someone explain the anwser?

Can someone explain the anwser?-example-1
User Pts
by
5.4k points

1 Answer

7 votes

Explanation:

To find each term, take the value of k (the term number) and multiply it by the square of the previous term.


c_(k)=k(c_(k-1))^(2),\ c_(0)=1\\\\c_(1)=1(c_(0))^(2)=1(1)^(2)\\c_(1)=1\\\\c_(2)=2(c_(1))^(2)=2(1)^(2)\\c_(2)=2\\\\c_(3)=3(c_(2))^(2)=3(2)^(2)\\c_(3)=12\\\\c_(4)=4(c_(3))^(2)=4(12)^(2)\\c_(4)=576\\\\c_(5)=5(c_(4))^(2)=5(576)^(2)\\c_(5)=1658880

User Enrico Gandini
by
5.7k points